Curcumin Co-Encapsulation Potentiates Anti-Arthritic Efficacy of Meloxicam Biodegradable Nanoparticles in Adjuvant-Induced Arthritis Animal Model - Bilal Aslam; Asif Hussain; Muhammad Naeem Faisal; Zia-ud-Din Sindhu; Rifat Ullah Khan; Ibrahim A. Alhidary; Shabana Naz; Vincenzo Tufarelli (Biomedicines, 2023)
This study aimed to evaluate the anti-arthritic activity of curcumin and meloxicam co-loaded PLGA nanoparticles in adjuvant-induced arthritic rats. PLGA nanoparticles encapsulating curcumin (nCur) and meloxicam (nMlx) alone and in combination (nCur/Mlx) were used to characterize zeta size and potential, polydispersity index, encapsulation efficiency (%), compound–polymer interactions (FT-IR analysis), and surface morphology (SEM imaging). In vivo, Complete Freund’s adjuvant-induced arthritic rats were intraperitoneally (i.p.) administered with curcumin, meloxicam, curcumin plus meloxicam, nCur, nMlx, and nCur/Mlx for 28 consecutive days. Results showed that nCur, nMlx, and nCur/Mlx significantly (p ≤ 0.05) reduced paw swelling and arthritic score, restored body weight and the immune organ index (thymus and spleen), as well as attenuated serum inflammatory markers (RF, CRP, and PGE2) and oxidative stress parameters (MDA, SOD, and CAT) in adjuvant-induced arthritic rats compared to free compounds. In addition, mono- and dual-compound-loaded nanoparticles significantly (p ≤ 0.05) down-regulated pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), up-regulated anti-inflammatory cytokines (IL-4, IL-10, and IFN-γ), and modulated OPG and RANKL expressions in paw tissue. The aforementioned results were further confirmed through radiological and histopathological examinations. Furthermore, the anti-arthritic effect of nCur/Mlx was notably (p ≤ 0.05) enhanced compared to nCur or nMlx alone. In conclusion, the co-nanoencapsulation of curcumin could potentiate the anti-arthritic activity of meloxicam and could provide a novel therapeutic approach for the formulation of nanocarrier pharmaceutical products for the management of arthritis.